Convergence or Borrowing: Standing in The Indonesian Constitutional Court - Hendrianto, Stefanus (The Constitutional Court of the Republic of Indonesia, 2015)
This Article addresses the constitutional convergence theory by examining the standing rule in the Indonesian Constitutional Court. The central investigation of this paper is whether the application of standing doctrine in the Indonesian Constitutional Court is evidence of constitutional convergence or of borrowing? This paper argues that the Constitutional Court jurisprudence on standing indicates that constitutional convergence has never taken place but rather the Court has engaged in constitutional borrowing. Legal borrowing on standing is limited to the carbon copy of the five-prong standing tests of the U.S. model, Â but in reality standing doctrine in the Indonesian Constitutional Court is not based on the private rights model of adjudication. Although the Court allows individuals to bring cases before the Court, it is rather a quasi-public model of standing, in which claimants no longer have standing only to vindicate their own private rights but can also sue to vindicate public interests. Standing requirements also allow the judges to review many highly sensitive political cases, and to Â some extent it enables the Court to second guess the decisions of the different branches of government.